2004
DOI: 10.1530/eje.0.1510151
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an alternative splicing transcript for the resistin gene and distribution of its mRNA in human tissue

Abstract: Objective: Adipocytes secrete a number of molecules such as tumor necrosis factor-alpha, leptin and free fatty acids that can influence the ability of the body to metabolize glucose. Recently, a novel 12.5 kDa cysteine-rich protein, termed resistin, was shown to be secreted by adipocytes. Resistin expression was markedly induced during the conversion of 3T3-L1 cells to mature adipocytes. Expression of resistin has been studied in human, mouse and rat; however, sequence information about an alternative splicing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
0
22
0
3
Order By: Relevance
“…An alternative explanation is that IGF-I may modulate the respective splicing and processing events of Rstn mRNA and protein and thereby lead to translocation of the Rstn protein, accumulation of the nonsecretable Rstn isoform, and a decrease in Rstn protein release. This assumption can be indirectly supported by recent evidence that a novel nonsecretable Rstn isoform lacking the exon 2 component has been reported in adipose tissues of Wistar rats (2), mice, and humans (34).…”
Section: Discussionmentioning
confidence: 71%
“…An alternative explanation is that IGF-I may modulate the respective splicing and processing events of Rstn mRNA and protein and thereby lead to translocation of the Rstn protein, accumulation of the nonsecretable Rstn isoform, and a decrease in Rstn protein release. This assumption can be indirectly supported by recent evidence that a novel nonsecretable Rstn isoform lacking the exon 2 component has been reported in adipose tissues of Wistar rats (2), mice, and humans (34).…”
Section: Discussionmentioning
confidence: 71%
“…RELM␤ expression is induced in the human colon cancer cell line LS174T by treatment with recombinant human IL-4 or IL-13 (1, 10), suggesting a potential role in the Th2 immune response. It is interesting to note that an alternative splice variant to a related molecule, resistin, is expressed in human lung (24). One previous study demonstrated that resistin can induce both mitogenesis and migration of human lung microvascular endothelial cells in vitro (23), and another showed that resistin induces proliferation of cultured human vascular smooth muscle cells (3).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the importance of the dimerization of Rstn in the regulation of adipogenesis. Recent evidence showed that secretable and nonsecretable Rstn isoforms were reported in adipose tissues of rats, mice, and humans (3,34). Thus it would be worthwhile in a future study to explore whether EGCG modulates the respective splicing and processing events of Rstn mRNA and protein and thereby leads to translocation of the Rstn protein.…”
Section: Discussionmentioning
confidence: 99%